2016
DOI: 10.1007/s12272-016-0836-3
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of atorvastatin and cyanidin-3-glucoside against angiotensin II-mediated vascular smooth muscle cell proliferation and migration through MAPK and PI3K/Akt pathways

Abstract: This study aimed to investigate the mechanism of cyanidin-3-glucoside (C3G) in synergy with atorvastatin, even when it is used in low concentrations. Human aortic smooth muscle cells (HASMCs) were used to verify the synergistic mechanism of atorvastatin and C3G against angiotensin II-induced proliferation and migration. BrdU incorporation assay was used to evaluate cell proliferation. Wound healing and Boyden chamber assays were used to investigate cell migration. The cell cycle was examined using flow cytomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Here, we used a model of HA-VSMC senescence induced by Ang II and verified that senescent HA-VSMCs enhanced migration and invasion, which was in agreement with previous reports regarding increasing migratory and invasive capacities in senescent rat VSMCs (24,37). Furthermore, it has been shown that Ang II can stimulate VSMC migration and invasion measured by a wound healing approach and Boyden chamber assay (20,21).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Here, we used a model of HA-VSMC senescence induced by Ang II and verified that senescent HA-VSMCs enhanced migration and invasion, which was in agreement with previous reports regarding increasing migratory and invasive capacities in senescent rat VSMCs (24,37). Furthermore, it has been shown that Ang II can stimulate VSMC migration and invasion measured by a wound healing approach and Boyden chamber assay (20,21).…”
Section: Discussionsupporting
confidence: 90%
“…Ang II is a major inductor of VSMCs senescence, and has been shown to potently simulate VSMCs migration and invasion (17)(18)(19)(20)(21). In addition, inhibition of Ang II pathways has been shown to substantially reduce ageassociated arterial remodeling (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated evidence shows PI3K phosphorylates Akt at Ser473 causing the kinase to be activated, and to mediate downstream signaling processes associated with cell growth and migration 44, 5558 , but has also been implicated in endothelium-dependent relaxation 41, 42 . More pertinently, eNOS has been found to be activated via the PI3K/Akt pathway by natural compounds like epigallocatechin-3-gallate 59 .…”
Section: Discussionmentioning
confidence: 99%
“…The synergistic effects of atorvastatin and cyanidin-3-glucoside improves HASMC proliferation and migration by enhancing cell cycle arrest through the AT 1R-mediated MAPK and PI3K/Akt pathways ( Pantan et al, 2016 ). FOXO3a phosphorylation plays an important role in mediating MMP-2 activation and VSMC migration.…”
Section: Pi3k-targeted Therapy In Atherosclerosismentioning
confidence: 99%